Integration of Multi-Item EOQ and EPQ to Minimize Total Inventory Cost of Outsole Raw Materials - Yahya Kusuma; Iriani Iriani (ITEJ (Information Technology Engineering Journals), 2025)
This study analyzes the integration of the multi-item Economic Order Quantity (EOQ) and Economic Production Quantity (EPQ) methods to minimize the inventory costs of outsole raw materials at UD. Santoso Mojokerto. The main problem lies in the high storage costs caused by the mismatch between purchasing quantities and the production needs of women’s flat sandals in sizes 37–39. Using demand, production, and inventory cost data for the period of August 2024–July 2025, EOQ is applied to determine the optimal order quantity, while EPQ is used to establish the optimal production quantity. The results show that integrating EOQ and EPQ can reduce total inventory costs compared to the company’s current method, while also maintaining raw material availability and ensuring smooth production processes.